Photodynamic properties and photoinactivation of Candida albicans mediated by brominated derivatives of triarylmethane and phenothiazinium dyes - Alvarez, María Gabriela (2014)
The photodynamic activity of brominated derivatives of New Fuchsin and Azure B was studied in solution and in cell suspensions of Candida albicans. The spectroscopic and photodynamic properties of these photosensitizers were compared with those of Crystal Violet and Azure B, which represent active photosensitizer related to each family of compounds. Triarylmethane derivatives absorb intensely with a band centered at ∼570 nm, while the phenothiazinium dyes at ∼650 nm. Photooxidation of 9,10-dimethylanthracene was observed using phenothiazinium compounds indicating the formation of singlet molecular oxygen, while it was not detected using triarylmethane agents. However, triarylmethane dyes were able to photooxidize l-tryptophan. In yeast cell suspensions, the photosensitized inactivation of C. albicans increases with photosensitizer concentration, causing a ∼5 log decrease of cell survival, when the cultures are treated with 20 μM of Crystal Violet and irradiated for 60 min. Under these conditions, the photodynamic activity of 50 μM Azure B induced a ∼3 log decrease of cell survival. Studies of photodynamic action mechanism indicated that photoinactivation of C. albicans cells induced by triarylmethane compounds involves mainly type I photoprocess. Although, phenothiazinium derivatives produce singlet molecular oxygen, a contribution of other reactive oxygen species cannot be discarded in the photoinactivation of C. albicans.